1988
DOI: 10.1116/1.584302
|View full text |Cite
|
Sign up to set email alerts
|

GaAs cleaning with a hydrogen radical beam gun in an ultrahigh-vacuum system

Abstract: GaAs surface cleaning prior to molecular-beam epitaxy (MBE) using a new hydrogen radical beam produced by an electron cyclotron resonance plasma in an ultrahigh-vacuum system is investigated. Residual oxygen and carbon on the GaAs surface after cleaning are monitored in situ with Auger electron spectroscopy. Oxygen and carbon, which are hard to remove by conventional thermal cleaning, can be removed by hydrogen radical (H*) beam irradiation at a substrate temperature of <400 °C. It is verified that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…(5) In combination with (2), this reaction seems to favor the formation of ZnTe patches on the sample surface, however, a continuous ZnTe coverage caused by exhausting the Cd in a complete layer on top of the CdZnTe substrate does not seem to take place during exposure times of a few 10 min as applied in this study. Hence, the roughening found for the etching of CdZnTe at higher temperature is attributed to patches of ZnTe which are partially resistant against the H 2 plasma etching at the expense of the CdTe component of the underlying CdZnTe.…”
Section: Temperature Effectsmentioning
confidence: 73%
“…(5) In combination with (2), this reaction seems to favor the formation of ZnTe patches on the sample surface, however, a continuous ZnTe coverage caused by exhausting the Cd in a complete layer on top of the CdZnTe substrate does not seem to take place during exposure times of a few 10 min as applied in this study. Hence, the roughening found for the etching of CdZnTe at higher temperature is attributed to patches of ZnTe which are partially resistant against the H 2 plasma etching at the expense of the CdTe component of the underlying CdZnTe.…”
Section: Temperature Effectsmentioning
confidence: 73%
“…Until recently, the study of AH cleaning processes on epi-ready semiconductor substrates have been mostly based on diffraction and/or spectroscopic analysis techniques [3,8,10,11], with only a relatively limited amount of evidence obtained using atomic resolution methods such as scanning tunnelling microscopy (STM) [3,7]. In this paper, we present our studies of the effects of AH exposure on the surface morphology and structure of epi-ready GaAs(0 0 1), GaAs(1 1 0) and GaAs(1 1 1)A substrates by reflection highenergy electron diffraction (RHEED) and STM.…”
Section: Introductionmentioning
confidence: 99%
“…Atomic hydrogen (AH) cleaning has been shown in a number of studies [1][2][3][4][5][6][7][8][9][10][11][12][13][14] to be a viable alternative method for the preparation of clean, atomically flat surfaces on a variety of III-V semiconductor substrates. The technique has several advantages over conventional thermal cleaning-much lower temperatures (p400 1C) are required; impurities (in particular oxide residues) are removed more rapidly and selectively; the procedure can be performed under UHV conditions; and the presence of a group V source is not required.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports showed that these experimental conditions for the atomic H cleaning on GaAs produce an atomically clean surface free of oxides. [12][13][14] The RHEED pattern was captured at 30 kV with an incident angle of 1 − 2°. The XPS data were recorded at intermediate steps in the sample preparation process using an Al K␣ 1 monochromatic source and a hemispherical analyzer.…”
mentioning
confidence: 99%